Diffusion coefficients of sodium dodecyl sulfate in water swollen cross-linked polyacrylamide membranes - Valente, A. J. M. (2002)
http://www.sciencedirect.com/science/article/B6TWW-4603M7T-5/1/856606240860bfc6cbe86dfc5f5b4bfb